Genetic polymorphisms (rs10636 and rs28366003) in metallothionein 2A increase breast cancer risk in Chinese Han population - Liu, Di (Aging (Albany NY), 2017)
Genetic polymorphisms of MT2A are frequently observed in many different cancers. We performed this case-control study, including 459 breast cancer (BC) patients and 549 healthy controls from Northwest China, to evaluate the associations between two common MT2A polymorphisms (rs10636 and rs28366003) and BC risk. The MT2A polymorphisms were genotyped via Sequenom MassARRAY. The individuals with the rs28366003 A/G, A/G-G/G genotypes underwent a higher risk of BC (P<0.0001). And, the minor allele G of rs28366003 was related to an increased BC risk (P<0.0001). We also found a significantly increased BC risk with rs10636 polymorphism among homozygote and recessive models (P<0.05). Further subgroup analysis by clinical characteristics of BC patients showed that Scarff, Bloom and Richardson tumor grade (SBR) 1-2 have a higher expression of the minor allele of these two MT2A loci than SBR 3. Our results indicated that the rs10636 and rs28366003 polymorphisms in MT2A increased BC risk in Northwest Chinese Han population.